Bangladesh Development Update, April 2014 - World Bank (Washington, DC, 2014)
Bangladesh moved closer to achieving the sixth five year plan target of reducing extreme poverty to 22.5 percent by 2015 as it sustained healthy gross domestic product (GDP) growth and moderate single digit inflation in FY2014. However, growth this year slowed relative to last year with declining remittances and losses due to political turmoil. Sound macroeconomic management kept inflation in check, although it increased somewhat due to the one-off effects of supply disruptions and wage increases. Official foreign exchange reserves increased to an adequate level as Bangladesh Bank intervened to keep the exchange rate stable. Weak demand for credit reduced interest rates. Monetary policy remained prudent while fiscal management challenged by shortfall in tax revenue, demand for support from sectors adversely affected by the political turmoil, and under-utilization of development budget. The fund's extended credit facility (ECF) is on track. Immediate challenges are to boost investments in power and roads; manage the transition in readymade garments; and stem the decline in remittances.